Formulasi Nanopartikel Verapamil Hidroklorida dari Kitosan dan Natrium Tripolifosfat dengan Metode Gelasi Ionik - Iswandana, Raditya; Anwar, Effionora; Jufri, Mahdi (Jurnal Farmasi Indonesia, 2013)
Nanopraticles can be prepared by several methods and the ionic gelation method is the easiest one. Verapamil hydrochloride is a drug which used as antiarrhythmic, antiangina, and antihypertension therapy. Nevertheless, bioavailability of orally administered verapamil is very low, only about 10 to 23%. Therefore, verapamil hydrochloride was prepared as nanoparticles dosage form to increase its Â bioavailability. The purpose of the present study was to optimize ionic gelation method of chitosan and sodium tripolyphosphate to obtain the best nanoparticles formulation. Nanoparticles were obtained from four different methods (formula A, B, C and D). Particle size distribution, zeta potential, entrapment efficiency, morphology, and fourier transform infra red spectrum of each nanoparticles formula were characterized. The chosen formula was formula D which has 62.8 nm of size, 59.15% of entrapment efficiency, Â±25.46 mV of zeta potential, spherical shape, and the ionic interaction was confirmed by FT-IR spectrum. The result showed that chitosan-tripolyphosphate succesfully produce the verapamil hydrochloride nanoparticles by ionic gelation method.Keywords: chitosan, ionic gelation, nanoparticles, sodium tripolyphosphate, verapamil hydrochloride